Analyzing the Cohesion and Adaptability of Families of Children with Intellectual Disability Using the FACES-20Esp Scale - Esther Vela Llauradó; Laura Serrano Fernández; Laura Martín Martínez (SAGE Open)
The impact of disability on families can vary greatly and depends directly on the coping ability of each family system. The purpose of this research is to analyze the functioning of 535 families of children with intellectual disability using the FACES-20Esp scale, identifying different types of families according to the variables of cohesion and adaptability. The results indicate that the style of family functioning can most commonly be classified as mid-range or unbalanced/extreme. Scores for cohesion are largely within the range of balanced; however, in terms of adaptability, the majority of families are considered unbalanced/extreme according to the model. The results of the study suggest there is a pressing need to provide families with strategies to face the challenges of raising and caring for a child with intellectual disability, and establish and maintain a balanced family system.